Probiotics enhance alveolar bone microarchitecture, intestinal morphology and estradiol levels in osteoporotic animals - Lucateli, R. L.; Silva, P. H.F.; Salvador, S. L.; Ervolino, E. [UNESP]; Furlaneto, F. A.C.; Marciano, M. A.; Antunes, T. B.M.; Del Arco, M. C.G.; Tardelli, M. D.C.; de Sousa, L. G.; Messora, M. R. (Wiley, 2024)
Background and Objective: Osteoporosis is associated with bone microarchitecture alterations, and the depletion of estrogen during menopause is a major contributing factor to its development. The literature highlights the noteworthy role of gut microbiota in bone metabolism, particularly in the progression of osteoporosis. Periodontal disease leads to alveolar bone loss, which may be influenced by estrogen deficiency, and this mechanism is intricately associated with an imbalance in systemic microbiota. The aim of this study was to evaluate the effects of Bifidobacterium animalis subsp. lactis HN019 (B. lactis HN019) and Lacticaseibacillus casei 01 (L. casei 01) administrations on an osteoporosis animal model. Materials and Methods: Thirty-three female rats were randomly divided into three groups: control (C-OVX), C-OVX-HN019 and C-OVX-LC01. All animals were ovariectomized. In groups C-OVX-HN019 and C-OVX-LC01, the probiotics were administered for 4 months. All animals were euthanized after 16 weeks from ovariectomy. Microtomographic, histopathological and immunohistochemical examinations were conducted on periodontal tissues, whereas histomorphometry, histopathological and immunohistochemical analyses were carried out on the intestine. The levels of estradiol were assessed in blood using an immunoenzymatic assay. The data were subjected to statistical analyses (p <.05). Results: The C-OVX-LC01 group exhibited a significant reduction in alveolar bone porosity and an increase in connective tissue density compared to C-OVX (p <.05). The C-OVX-HN019 and C-OVX-LC01 groups presented reduced expression of TRAP and RANKL compared to the C-OVX (p <.05). The C-OVX group presented villi defects, mild neutrophil infiltration, decrease in both villous height and intestinal crypts and reduced expression of intestinal junctional epithelium markers e-cadherin and claudin 01 compared to C-OVX-HN019 and C-OVX-LC01 (p <.05). The C-OVX group had lower estradiol levels than C-OVX-HN019 and C-OVX-LC01 (p <.05). Conclusion: The probiotic therapy promoted a reduction in alveolar bone destruction and intestinal permeability as well as an increase in estradiol levels in ovariectomized rats. Specifically, the probiotic strain Lacticaseibacillus casei 01 exhibited greater effectiveness compared to Bifidobacterium animalis subsp. lactis HN019, indicating strain-dependent outcomes.
Keywords: Alveolar bone; intestinal; probiotics; rats